Pengaruh Kualitas Produk, Harga dan Promosi Terhadap Keputusan Pembelian Sneakers Brand Lokal - Sri Manik Parasari, Nyoman; Chandra Mandira, I Made; Mira Yanti, Ni Putu (Jurnal Dinamika Ekonomi dan Bisnis, 2024)
The aim of this study is to investigate the impact of price, promotion, and product quality on consumers' purchasing decisions when it comes to Ventela, a local brand specializing in sneakers. Once buyers have made a purchase, they will evaluate their level of satisfaction or disappointment with the product upon receiving it. This study was conducted in Denpasar City, employing quantitative research approach. The target population was all students in Denpasar who wore Ventela shoes, and 119 participants were chosen utilizing the representative selection method using the formula by Hair et al. This research utilized quantitative data obtained from both primary (questionnaire answers) and secondary (sales data) sources. The data were collected by examining the usage of social media and the Ventela shoe sales platform, analyzing data on top local shoe brands, and comparing prices of Ventela shoes. To gather data for this study, a questionnaire designed on Google Forms was distributed. Additionally, traditional statistical tests such as the assumption test, multiple linear regression test, t test, F test, and coefficient of determination were applied in this research. The findings of this study indicated that the purchasing decisions of consumers were influenced in a positive and significant manner by the quality, price, and promotion of a product. The test results indicated that the quality of the Ventela brand sneakers had a significant and positive impact on purchasing decisions. The decision to purchase Ventela sneakers, a local brand, was affected by price, promotion, and the of product quality